Everyone Should be Fatactivists or Fat-allies - Amlund, Dina (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
Fatphobia is ubiquitous. Fatphobia is a structure in society. And it affects the lives of fat people in ways that are damaging to their health and can cause major inequities. This article maps out fatphobia as ever present through the history of Western culture – no time period exceptions – and it examines a very important report from the World Health Organization (WHO) concerning the health hazard and social inequities caused by fatphobia. Shakespeare’s fatjokes and the ever presence of shapewear and all the portraits of Jesus as a thin, white man show us 5,000 years of cultivated fatmisia. That is why WHO has written a report urging doctors and other healthcare professionals to treat fat patients with empathy and sensitivity like they would thin patients. In mapping out a structure that dehumanises people of size, I bring in a few examples from my own life as a fat person and as a fatactivist. Existing while fat in a world that hates fatness is hard work.